Recurrent Sclerema in a Young Infant Presenting with Severe Sepsis and Severe Pneumonia: An Uncommon but Extremely Life-threatening Condition (Journal of Health, Population and Nutrition, 2014)
A one month and twenty-five days old baby girl with problems of acute watery diarrhoea, severe dehydration, severe malnutrition, and reduced activity was admitted to the gastrointestinal unit of Dhaka Hospital of icddr,b. The differentials included dehydration, dyselectrolytaemia and severe sepsis. She was treated following the protocolized management guidelines of the hospital. However, within the next 24 hours, the patient deteriorated with additional problems of severe sepsis, severe pneumonia, hypoxaemia, ileus, and sclerema. She was transferred to the Intensive Care Unit (ICU). In the ICU, she was managed with oxygen supplementation, intravenous antibiotics, intravenous fluid, including a number of blood transfusions, vitamins, minerals, and diet. One month prior to this admission, she had been admitted to the ICU also with sclerema, septic shock, and urinary tract infection due to Escherichia coli and was discharged after full recovery. On both the occasions, she required repeated blood transfusions and aggressive antibiotic therapy in addition to appropriate fluid therapy and oxygen supplementation. She fully recovered from severe sepsis, severe malnutrition, ileus, sclerema, and pneumonia, both clinically and radiologically and was discharged two weeks after admission. Consecutive episodes of sclerema, resulting in two successive hospitalizations in a severely-malnourished young septic infant, have never been reported. However, this was managed successfully with blood transfusion, broad-spectrum antibiotics, and correction of electrolyte imbalance. DOI: http://dx.doi.org/10.3329/jhpn.v31i4.20053 J HEALTH POPUL NUTR 2013 Dec; 31(4): 538-542